Novel and Recurrent Mutations in a Cohort of Chinese Patients With Young-Onset Amyotrophic Lateral Sclerosis - Deng, Jianwen; Wu, Wei; Xie, Zhiying; Gang, Qiang; Yu, Meng; Liu, Jing; Wang, Qingqing; Lv, He; Zhang, Wei; Huang, Yining; Wang, Tao; Yuan, Yun; et al. (Frontiers in Neuroscience, 2019)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease that affects nerve cells in the brain and spinal cord. More than 25 ALS-related genes have been identified, accounting for approximately 10% of sporadic ALS (SALS) and two-thirds of familial ALS (FALS) cases. Several recent studies showed that genetic factors might have a bigger contribution to young-onset ALS in comparison to ALS cases overall. However, the genetic profile of young-onset ALS patients is not yet fully understood. Here, we investigated a cohort of 27 young-onset ALS patients (onset age <45 years) by whole-exome sequencing (WES). Genetic analysis identified pathogenic variants of FUS (25.9%), SOD1 (22.2%), TARDBP (3.7%), VCP (3.7%) in 27 young-onset ALS patients. Out of 12 types of identified mutations, c. 1528A>C in FUS and c. 266G>A in VCP were novel. All cases in this study reflect a monogenic origin with an autosomal dominant mode of inheritance. Notably, a novel de novo missense mutation, c.1528A>C (p.K510Q), in FUS was identified in a 29-year-old ALS patient. Expression of the K510Q mutant FUS resulted in cytoplasmic mislocalization of FUS in cultured cells and induced neural toxicity in a fly model. This study provided further evidence of the genetic profile of young onset ALS patients from China, and expanded the mutational spectrum of FUS gene with one new K510Q mutation identified.